Perencanaan Karir Siswa Ditinjau Dari Jenis Kelamin - Dwi Wahyanti; Sisca Folastri (Psychocentrum Review, 2021)
Objective study to determine career planning of male and female students, as well as to determine whether there are differences in career planning between male and female students of class XI SMK Islam Wijaya Kusuma. Research method is quantitative approach with a comparative method. Data and data sources were students of class XI SMK Islam Wijaya Kusuma, totaling 120 students out of 156 students. This study uses career planning instrument. The data analysis technique used is t test. The results showed career planning for male students of class XI SMK Islam Wijaya Kusuma in medium category and career planning for female students  in the high category. The results also showed there significant differences in the career planning of male and female students of class XI SMK Islam Wijaya Kusuma. This is evidenced by the t count of 13.751> t table of 1.65787 at α = 0.05.